Role of the HIF‐1α/Nur77 axis in the regulation of the tyrosine hydroxylase expression by insulin in PC12 cells. Issue 7 (7th December 2018) - Fiory, Francesca; Mirra, Paola; Nigro, Cecilia; Pignalosa, Francesca Chiara; Zatterale, Federica; Ulianich, Luca; Prevete, Nella; Formisano, Pietro; Beguinot, Francesco; Miele, Claudia
Abstract: Tyrosine hydroxylase (TH), catalyzing the conversion of tyrosine into l ‐DOPA, is the rate‐limiting enzyme in dopamine synthesis. Defects in insulin action contribute to alterations of TH expression and/or activity in the brain and insulin increases TH levels in 1‐methyl‐4‐phenylpyridinium (MPP+)‐treated neuronal cells. However, the molecular mechanisms underlying the regulation of TH by insulin have not been elucidated yet. Using PC12 cells, we show for the first time that insulin increases TH expression in a biphasic manner, with a transient peak at 2 hr and a delayed response at 16 hr, which persists for up to 24 hr. The use of a dominant negative hypoxia‐inducible factor 1‐alpha (HIF‐1α) and its pharmacological inhibitor chetomin, together with chromatin immunoprecipitation (ChIP) experiments for the specific binding to TH promoter, demonstrate the direct role of HIF‐1α in the early phase. Moreover, ChIP experiments and transfection of a dominant negative of the nerve growth factor IB (Nur77) indicate the involvement of Nur77 in the late phase insulin response, which is mediated by HIF‐1α. In conclusion, the present study shows that insulin regulates TH expression through HIF‐1α and Nur77 in PC12 cells, supporting the critical role of insulin signaling in maintaining an appropriate dopaminergic tone by regulating TH expression in the central nervous system. Abstract : Insulin positively regulates tyrosine hydroxylase expression in PC12 cells in a biphasic manner by activating in turn hypoxia‐inducible factor 1‐alpha and nerve growth factor IB.